Chopper offset stabilized current sensing amplifier - Low, Thien Shawn (Nanyang Technological University, 2024)
Current sensing is an indispensable technique employed across various uses, prominently in facilitating energy conservation, protection, and motor drives. It serves as a critical tool for ensuring safety and optimizing the performance of industrial machines, motors and other applications. The design of current sensing amplifier demands low offset, which is hard to achieve without using dynamic offset compensation techniques. However, commonly employed methods such as chopping stabilisation and auto zero present several challenges. At current state of art, auto zero does not deteriorate transient speed by employing ping pong approach. However, it requires a considerable area to achieve similar offset reduction compared to chopper offset stabilisation. Additionally, it introduces noise folding which exacerbates the white noise. While chopping stabilisation technique offers significant noise and offset reduction, they lead to long settling time due to the addition of low pass filter or ripple reduction techniques to reduce the ripple voltage. To have the benefit of chopping stabilisation noise reduction while maintaining fast transient response, chopper offset stabilisation had been proposed. The aim of this project is to design a current sensing amplifier with low offset, low noise, and good transient speed without sacrificing a large area. To circumvent the issues brought by other dynamic offset compensation techniques, chopper offset stabilization technique is employed. It operates by having two-frequency path where one of the paths is dynamic offset compensated to compensate the offset of another path. This ensures the transient speed of the amplifier will not be affected by dynamic offset compensation and ensure continuous operation of the current sense amplifier without sacrificing large area. In this project, the offset of the amplifier can reduce below 5 with a transient speed of 2 s which has met the design specifications while ensuring large current sensing range. In this project, the current sensing amplifier will be used in latching current limiter to provide the exact loading current information for the user about the downstream loads. This information can be further processed by the FPGA after ADC digitizing.